Dante beyond influence : rethinking reception in Victorian literary culture - Coluzzi, Federica (Interventions: rethinking the nineteenth century (Series), 2021)
Dante beyond influence is the first study to conceptualise and historicise the hermeneutic turn in Dante reception history and Victorian cultural history, charting its development across intellectual realms, agents and forms of readerly and writerly engagement. Unearthing previously unseen manuscript and print evidence, the book conducts a material and book-historical inquiry into the formation and popularisation of the critical and scholarly discourse on Dante through Victorian periodicals, mass-publishing, traditional and Extramural higher education. The book demonstrates that the transformation of Dante from object of amateur interest (dantophilia) to subject of systematic interpretive endeavours (dantismo) reflected paradigmatic changes in Victorian intellectual and socio-cultural history.--